A Feasibility study on St. Dominic Savio School for Special Children - Asio, Manuel P. Jr; Carreon, John Philip Q.; Guevara, Ma. Paz S.; Padua, George O.; Potenciano, Joan Mary S. (College of Engineering, 1992)
Every individual has a right to a relevant quality education and every child with special needs has a right to an educational program suited to his needs. St. Dominic Savio School (named after the young saint from Becci, Italy) wishes to cater to the needs of these special children, specifically the mentally handicapped. The proponents of this project believe that these individuals can be more dependent and useful in society than is expected and that with the proper guidance and approach, these people would be able to develop to their maximum potential. In line with the government's objective of providing education for everyone, the project was conceptualized and has been studied. It also wishes to open the eyes of the general public regarding this fact which is usually ignored and to which a great number of us is apathetic about. Hopefully, in the years to come this aspect of society would be treated more favorably and that more services for the mentally handicapped would be provided. The proponents of this project centered more on the social impact that this project would bring and not on profitability of engaging in such service. The purpose of this study is to explore into the feasibility of establishing a school for the mentally retarded with the aim of integrating them in a regular school system and the community. This will be done through the innovative teaching methods, tools and techniques to be used by the school. Saint Dominic Savio School for Special Children is situated in Alabang Hills, a residential area. This site was chosen on the bases of proximity to the market, accessibility, conduciveness to learning, availability of utilities and price of land. The facility is to be fully operational in the year 1994, opening in that academic year. Time considerations for construction and promotion was made. There are five major parts of the study that would tell us whether the project is feasible or not, namely the market, technical, financial, socio-economic and managerial feasibility. In a given geographical area, ten percent consists of physically and mentally handicapped individuals. Of this percentage, 30-70 percent consists of physically and mentally handicapped individuals. Of this percentage, 30-70 percent are mentally retarded. This is a generally accepted standard set by the UNICEF and WHO, being used in Asia and the Philippines. The target are for delivery of service is Metro Manila. Savio School would be catering to the A-B class mentally retarded individuals with ages ranging from 8 to 18 years old (the development period). The demand for the service was determined with the use of data gathered on population from the National Statistics Office. It was evident from this information that there is a big need for special education for the mentally handicapped. According to the records from the DECS, the number of these children enrolled in different institutions and schools is only a small percentage of the total. Also, most of the existing schools are for public and as such, may not be giving the proper education needed by their student. With the continuous growth of the Philippine population, the demand does not only increase exponentially with it, but the difference in the demand and the supply becomes nearly irreconcilable. It was concluded from the analysis of the market that the project is marketable feasible. In the course of the student's stay in the school, he will be passing through three stages. Assessment and evaluation of his capabilities would first be done. This would be necessary for designing the appropriate program for each student. As he progresses through grade school, constant evaluation of his performance will be made to monitor his improvement. When he graduates from the school, referrals would be made for further studies in vocational schools through linkages. Since the main input in the project is manpower, there will be no difficulty in the technical aspect because there is a supply of SPED teachers. Aside from this, the school would be providing continuous training for all its employees. Materials for teaching and the curricula to be used are patterned after the recommendation of the DECS. This makes that study technically feasible. At the first couple of years, it is shown in the pro-forma income statement that the school would be incurring a loss. However, depreciation which has been included in the computation of expenses is not actually spent by the company and as a result, the school would still be earning liquid assets. The total project cost would be amounting to about 8 million pesos and it is assumed that the proponents of the project would have an initial capital totaling to about 5.4 million to be used for acquiring land which in turn, will be used as collateral for getting a loan. There are different sources of financing and there are different corresponding loan interest rates as well. Money would be borrowed from the Development Bank of the Philippines which has the lowest interest rate and is most able in providing the project a loan. From the analysis of the financial statements, the projects financial feasibility was concluded to be sound. It is the policy of the DECS that special schools be owned by a non-stock, non-profit corporation. Expenses and capital in this type of organization is hared by a group of people called the incorporators. Management of the school would be handled by these people with a reshuffling of positions after certain periods. As a whole, the project has been proven to be feasible and it is evident that it will make a good contribution to society. Although the project may not be profitable in terms of monetary returns, its profitability can be measured with each warmed heart of the students' parents and with each smiling face of the children it will help.